The Bulk Metric in the Theory with Two Extra Dimensions - Phat, Tran Huu; Lien, Phan Hong; Chung, Ha Van (Communications in Physics, 2014)
The metric of a warped space-time with two extra dimensions is established by means of the Einstein equations in six dimensions and the compactification of two extra dimensions on a square . It is shown that at every among two fixed points our manifold reduces to the five-dimensional Randall - Sundrum space - time and the hierarchy problem could be solved .